ON HALF EXPONENTIAL POWER MODEL FOR THE FIRST TIME FAILURE OF POWER DISTRIBUTION TRANSFORMERS IN NIGERIA - Olosunde, Akinlolu; Ekpo, Rowland Benjamin (Indonesian Journal of Statistics and Applications, 2020)
Transformer failure is a major problem confronting the Nigerian power sector, hindering the transmission and distribution of electric power to various households, institutions, and industries. Many of these transformer developed problem due to the old age of the transformers, overloading, in-availability of technical expertise, poor maintenance culture, manufacturer's faults, just to mention few. The present research focuses on providing half exponential power model for the failure of already installed transformers, with respect to years of installation up to the time of the first failure, using secondary data from the south western part of Nigeria as a case study. The results obtained showed that half exponential power performed better in modeling the first time failure of power transformers. This was possible because of the present of shape parameter which gives flexibility to half exponential power when compared with a half normal distribution.